-6=(1/3)+x

Simple and best practice solution for -6=(1/3)+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6=(1/3)+x equation:



-6=(1/3)+x
We move all terms to the left:
-6-((1/3)+x)=0
Domain of the equation: 3)+x)!=0
x!=0/1
x!=0
x∈R
We add all the numbers together, and all the variables
-((+1/3)+x)-6=0
We multiply all the terms by the denominator
-((+1-6*3)+x)=0
We calculate terms in parentheses: -((+1-6*3)+x), so:
(+1-6*3)+x
determiningTheFunctionDomain x+(+1-6*3)
We add all the numbers together, and all the variables
x+(-17)
We add all the numbers together, and all the variables
x-17
Back to the equation:
-(x-17)
We get rid of parentheses
-x+17=0
We add all the numbers together, and all the variables
-1x+17=0
We move all terms containing x to the left, all other terms to the right
-x=-17
x=-17/-1
x=+17

See similar equations:

| -3h+1=-7 | | 2+2(1-6b)=64 | | 5x+2=-11 | | 92=20+9r | | 6(x-7)=4x+-8 | | 6n=4n-18 | | 2/5n+1=1/2n+2 | | 28-x=17-3x | | x+.65x=200 | | 26x+7=5(5x+5) | | 8=9y+4-2y | | 5(4+4r)=140 | | 2w+8=1 | | 10x+20=3(3x+4) | | 2.2+10m=8.91 | | 3/8=-9/4x | | 2(4x-3)=7x+-6 | | 2(10-6h=h-8 | | 25t+5=25t-7 | | 8x-2x+6=x-7+13 | | 70+7x=14+14x | | 6/5(m/1)=26 | | Z-15=3z | | 8x-2-3x=x+8+x | | 0.8+y=2.9 | | 2.4+10m=7.31 | | 5n+7=2n+12 | | 4y=14=2y-4 | | 3/4×x=6 | | 7x-(2x+20)=15 | | 12h=288 | | 14(8x+16)-3x=33 |

Equations solver categories